Metabolic Effects of FGF-21: Thermoregulation and Beyond - Ni, Bin; Farrar, Jared S.; Vaitkus, Janina A.; Celi, Francesco S. (Frontiers in Endocrinology, 2015)
FGF-21, a member of the fibroblast growth factor (FGF) family, is a novel hormone involved in the control of metabolism by modulating glucose homeostasis, insulin sensitivity, ketogenesis, and promoting adipose tissue “browning”. Recent studies demonstrated that brown adipose tissue is not only a target for, but is also a potentially important source of systemic FGF-21. These findings support the hypothesis that FGF-21 plays a physiologic role in thermogenesis and thermogenic recruitment of white adipose tissue by an autocrine-paracrine axis. This review examines the role of FGF-21 in thermogenesis from the perspective of cell-based, animal model, and human studies. We also present recent advances in the characterization of FGF-21’s regulation of metabolism.